1982
DOI: 10.1104/pp.69.6.1268
|View full text |Cite
|
Sign up to set email alerts
|

H2 and CO2 Evolution by Anaerobically Adapted Chlamydomonas reinhardtii F-60

Abstract: Using manometric and enzymic techniques, H2 and CO2 evolution in darkness and light has been studied in the green alga Chianydomonas reinhardtii F-60. F-60 is a mutant strain characterized by an incomplete photosynthetic carbon reduction cycle but an intact electron transport chain.In the dark, starch was broken down, and H2 and CO2 was released. The uncoupler, carbonyl cyanide m-fluorophenylhydrazone with an optimum concentration of 5 to 10 micromolar, increased the rate of CO2 release and starch breakdown bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Starch mobilization has been implicated in H 2 production from green algae (Healey, 1970;Bamberger et al, 1982;Gfeller and Gibbs, 1984;Ohta et al, 1987;Kosourov et al, 2001;Melis and Happe, 2001); however, our work directly links the disruption of a specific enzyme involved in starch metabolism to attenuated H 2 photoproduction. Two different metabolic pathways provide reductant used in the photoproduction of H 2 by algal cells anaerobically induced in the dark.…”
Section: Starch and Hydrogen Productionmentioning
confidence: 67%
See 1 more Smart Citation
“…Starch mobilization has been implicated in H 2 production from green algae (Healey, 1970;Bamberger et al, 1982;Gfeller and Gibbs, 1984;Ohta et al, 1987;Kosourov et al, 2001;Melis and Happe, 2001); however, our work directly links the disruption of a specific enzyme involved in starch metabolism to attenuated H 2 photoproduction. Two different metabolic pathways provide reductant used in the photoproduction of H 2 by algal cells anaerobically induced in the dark.…”
Section: Starch and Hydrogen Productionmentioning
confidence: 67%
“…Two different metabolic pathways provide reductant used in the photoproduction of H 2 by algal cells anaerobically induced in the dark. One of the pathways originates in PSII-catalyzed water oxidation (Bamberger et al, 1982;Greenbaum et al, 1983;Gfeller and Gibbs, 1984), and it is sensitive to the PSII inhibitor DCMU. This pathway involves the full photosynthetic electron transport chain.…”
Section: Starch and Hydrogen Productionmentioning
confidence: 99%
“…Another aspect of interest here is the anaerobic stimulatory effect of acetate on the release of CO2 and H2 in the light by C. reinhardii (3) and by other green algae ( 18,21 acetate requires ATP, Bamberger et al (3) suggested that acetate increased gas production by consuming ATP which regulated the unspecified sequence of reactions giving rise to CO2 and H2. Healey (18) modifying a mechanism put forward by Jones and Myers (20) to explain the Kok effect in blue-green algae, proposed a flow of electrons from acetate via the citric acid cycle into PSI resulting in the photoevolution of H2 from reduced Fd.…”
mentioning
confidence: 99%
“…On the other hand, Hirt et al (15) demonstrated that light can inhibit severely the rate of anaerobic glycolysis in Scenedesmus obliquus as monitored by D-lactic acid formation. Bamberger et al (2) made use of C. reinhardtii F-60, a mutant characterized by an incomplete photosynthetic carbon reduction pathway but an intact photosynthetic electron transport chain, to monitor 'true' CO2 and H2 evolution. To account for their results, they proposed an involvement between anaerobic carbohydrate metabolism and the photosynthetic electron transport chain, implying that carbohydrate degradation is entirely or partially localized in the chloroplast.…”
mentioning
confidence: 99%